Urea toxicity associated with urea-molasses block feeding in lambs in the central highland of Ethiopia - Tibbo, Markos; Amare, H.; Haile, Aynalem; Mukasa-Mugerwa, E. (1998)
The paper reports on accidental urea toxicity in lambs associated with group feeding of urea-molasses block (UMB). The feeding method, the estimated toxic dose, and the incident of toxicity are described. The clinical signs, treatment, outcome, and gross pathological findings are discussed. The danger involved in group feeding of UMB and other non-protein nitrogen (NPN) supplements is stressed, and the possible ways of preventing toxicity are suggested.